Circular economy supply chains : from chains to systems - Bals, Lydia; Tate, Wendy L.; Ellram, Lisa M. (Emerald Publishing Limited, 2022)
A circular economy perspective embraces a notion that we design everything to be reused for as long as possible, and then recaptured and repurposed when reuse is no longer possible. Designing for a circular economy ecosystem requires a more holistic, integrative viewpoint, spanning all aspects of design and development and considering many supply chain actors, far beyond that of traditional supply chains. Circular Economy Supply Chains highlights the need for cross-industry flows and the need for different actors (beyond producers and consumers) in circular value cycles. While biomimicry provides the structure for organizing the book, individual chapters build on other theoretical lenses and concepts, such as stakeholder theory. This book intends to move beyond a buyer-supplier view, embracing a holistic network or ecosystem view, to consider a cross-industry system perspective, where there is a diversity of actors needed for a working ecosystem. This edited book offers a comprehensive overview of system components and actors, including how the circular economy adds value, the role of producers and consumers, the spectrum of recovery possibilities to return products back to the consumption supply chain, and the essential role of information management.